2020
DOI: 10.1177/1087054720964578
|View full text |Cite
|
Sign up to set email alerts
|

Children With ADHD Are at Risk for a Broad Array of Adverse Adult Outcomes That Cross Functional Domains: Results From a Population-Based Birth Cohort Study

Abstract: Objective: To identify patterns (“classes”) of outcomes for adults with and without childhood ADHD. Method: Subjects were 232 childhood ADHD cases and 335 non-ADHD referents from a 1976 to 1982 birth cohort. We used latent class analyses to identify classes based on a broad array of adult psychosocial outcomes and determined the proportion of subjects with childhood ADHD within each class. Results: A three class solution provided optimal model fit; classes were termed “good,” “intermediate,” and “poor” functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
1
3
0
1
Order By: Relevance
“…The important differences found in our study in social situation, educational level, source of income and personal security in life have earlier been described for mostly clinically referred women with ADHD ( Owens et al, 2017 ; Uchida et al, 2018 ). A population- based study reported recently that childhood ADHD is associated with adverse adult outcome in many areas which accords with the findings of the present study ( Harstad et al, 2022 ). We have not been able to find any previous study on psychosocial status with regard to highly functioning women with ASD.…”
Section: Discussionsupporting
confidence: 93%
“…The important differences found in our study in social situation, educational level, source of income and personal security in life have earlier been described for mostly clinically referred women with ADHD ( Owens et al, 2017 ; Uchida et al, 2018 ). A population- based study reported recently that childhood ADHD is associated with adverse adult outcome in many areas which accords with the findings of the present study ( Harstad et al, 2022 ). We have not been able to find any previous study on psychosocial status with regard to highly functioning women with ASD.…”
Section: Discussionsupporting
confidence: 93%
“…Their immediate impacts on education and childhood development lead to poorer outcomes later in life. For example, adults who were diagnosed with ADHD in childhood are less likely to graduate high school or pursue college or vocational training (Uchida et al, 2018), more likely to be fired or to be treated for alcohol or drug use (Harstad et al, 2022), and are also overrepresented in prison populations (Young et al, 2015). Contrary to the focal article, which states that the three types of neuroatypicality are "unrelated to overall cognitive ability" (p. 23), ASD and ADHD are related to lower cognitive abilities and intellectual functioning.…”
Section: Overemphasis On High-functioning Neuroatypical Outliersmentioning
confidence: 99%
“…Longitudinal data have shown that early onset ADHD is consistently associated with emotional problems throughout childhood (Stern et al, 2020), and it exerts a significant impact on functioning during adulthood (Harstad et al, 2020). Cohort studies revealed hyperactive, impulsive, and inattention symptoms as risk factors for adult intimate partner violence (Buitelaar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%